Studies on the thermoluminescence glow curves of Mn doped ZnS nanoparticles - Sharma, Ravi (Recent Research in Science and Technology, 2012)
This paper reports the synthesis of ZnS nanoparticles doped with Mn using mercaptoethanol (ME) as the capping agent. The particle size of such nanoparticles were measured by X-ray diffraction technique (XRD) and by the Transmission electron microscopy (TEM) patterns and were found to be in between 2nm - 6nm. For the samples with different concentration of the capping agent, it was found that the thermoluminescence (TL) intensity of ZnS:Mn nanoparticles increased as the particle sizes were decreased. The shift in peak position of TL glow curve was also seen with decreasing particle size.